2014
DOI: 10.1111/ijn.12321
|View full text |Cite
|
Sign up to set email alerts
|

Resilience in families of children with Down syndrome in Korea

Abstract: This study aims to identify the factors related to resilience of the families of children with Down syndrome (DS). Data were collected from 126 parents of children with DS in Korea, using a self-administered questionnaire. The age of the child, developmental level of the child, parental depression, and stress and strain were negatively related with family adaptation, whereas health of parents, family cohesiveness, flexibility, communication skills, supportive family/relatives, and quality of community service … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(68 citation statements)
references
References 26 publications
1
60
0
2
Order By: Relevance
“…Only four studies identified their guiding framework; two used family frameworks, the Resiliency model (Hsiao & Van Riper , Choi & Van Riper ) and Patterson's family resilience model (Choi & Yoo ) and one used an individual‐centric framework, the stress and coping model (Lam & Mackenzie ). Two studies were comparative (Cheng & Tang , Gau et al .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Only four studies identified their guiding framework; two used family frameworks, the Resiliency model (Hsiao & Van Riper , Choi & Van Riper ) and Patterson's family resilience model (Choi & Yoo ) and one used an individual‐centric framework, the stress and coping model (Lam & Mackenzie ). Two studies were comparative (Cheng & Tang , Gau et al .…”
Section: Resultsmentioning
confidence: 99%
“…While only one level of adaptation was assessed in most studies, (Cheng & Tang , Choi et al . , Choi & Van Riper , Hsiao ), two levels were assessed in two studies (Hsiao & Van Riper , Choi & Yoo ) and all three levels (individual, dyadic and family) were assessed in two studies (Chiu et al . , Gau et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…27 Furthermore, according to cultural differences, Korean parents take full responsibility for their child's care because support programs for children with chronic condition in Korea are still very limited. 28 For this reason, they seem to be more overprotective of their child and it led to be more proactive in the bowel management of their children comparing with adult/elderly population. It was essential that a designated specialized nurse practitioner provides structured follow-up of the children.…”
Section: Resultsmentioning
confidence: 99%